2020
DOI: 10.1101/2020.01.10.902205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An amygdalo-parabrachial pathway regulates pain perception and chronic pain

Abstract: The parabrachial (PB) complex mediates both ascending nociceptive signaling and descending pain modulatory information in the affective/emotional pain pathway. We have recently reported that chronic pain is associated with amplified activity of PB neurons in a rat model of neuropathic pain. Here we demonstrate that similar activity amplification occurs in mice, and that this is related to suppressed inhibition to PB neurons from the central nucleus of the amygdala (CeA). Animals with pain after chronic constri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 91 publications
6
40
1
Order By: Relevance
“…Since the LPBN also receives GABAergic innervation from other brain regions 28,53,54 , it was possible that light stimulation in the vGAT-ChR2 transgenic mice activated the fibers and terminals of GABAergic neurons projecting to or via the LPBN from other brain regions. To determine whether activation of the local GABAergic LPBN neurons is sufficient to inhibit neuropathic pain-like hypersensitivity, we initially injected Credependent AAV-DIO-ChR2-eYFP or AAV-DIO-eYFP virus into the LPBN of mice expressing Cre recombinase under the control of the glutamic acid decarboxylase enzyme (GAD2-ires-Cre mice) ( Fig.…”
Section: Inactivation Of Glutamatergic Lpbn Neurons Alleviates Both Bmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the LPBN also receives GABAergic innervation from other brain regions 28,53,54 , it was possible that light stimulation in the vGAT-ChR2 transgenic mice activated the fibers and terminals of GABAergic neurons projecting to or via the LPBN from other brain regions. To determine whether activation of the local GABAergic LPBN neurons is sufficient to inhibit neuropathic pain-like hypersensitivity, we initially injected Credependent AAV-DIO-ChR2-eYFP or AAV-DIO-eYFP virus into the LPBN of mice expressing Cre recombinase under the control of the glutamic acid decarboxylase enzyme (GAD2-ires-Cre mice) ( Fig.…”
Section: Inactivation Of Glutamatergic Lpbn Neurons Alleviates Both Bmentioning
confidence: 99%
“…It is interesting to note that GABAergic neurons only constitute~10.1% of LPBN neurons, much less than that reported in the spinal dorsal horn (~70%) 62 and in the central nucleus of the amygdala (~50.78%), but comparable to that reported in the thalamus (~10.43%) and somatosensory cortex (~8.66%) (Allen Brain Atlas, http://www. brain-map.org) in the pain transmission pathway, suggesting that glutamatergic LPBN neurons that also receive GABAergic innervation from other regions 28,54,53 are under the relatively weak control of local GABAergic neurons. Consistent with this proposal, we found that the optogenetic activation of GABAergic LPBN neurons did not affect the paw-withdraw response in naïve mice (Fig.…”
Section: Prementioning
confidence: 99%
See 2 more Smart Citations
“…The suppressed release of GABA may lead to the amplified activity of PB neurons, seen in chronic pain conditions (Uddin et al, 2018;Raver et al, 2020) through at least two mechanisms. Reduced GABA release may lead to reduced activation of postsynaptic GABA B receptors, resulting in dis-inhibition of PB neurons and amplifying responses to nociceptive inputs (Uddin et al, 2018;Raver et al, 2020).…”
Section: Gaba B Receptors Diminish Pre-and Postsynaptic Excitabilitymentioning
confidence: 99%